2013
DOI: 10.2147/dddt.s41423
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of entecavir for chronic hepatitis B in Chinese patients

Abstract: The People’s Republic of China has one of the highest rates of hepatitis B virus (HBV) infection. This review summarizes recent data from studies of entecavir, one of the recommended first-line oral therapies for treating chronic hepatitis B, in Chinese HBV-infected patients. Long-term treatment with entecavir is efficacious and well tolerated, and studies comparing entecavir with other nucleos(t)ide therapies, such as lamivudine, adefovir, and telbivudine, demonstrate superior antiviral effects for entecavir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The basic patent for ETV-Brand in the USA was invalidated in 2014 [ 28 ]. In China and Brazil, the basic patents expired in 2011 [ 29 ]. In terms of price, generic ETV can be more feasible in developing or undeveloped country [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basic patent for ETV-Brand in the USA was invalidated in 2014 [ 28 ]. In China and Brazil, the basic patents expired in 2011 [ 29 ]. In terms of price, generic ETV can be more feasible in developing or undeveloped country [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among the 182 patients who were prescribed with entecavir and were also measured with medium or low adherence, approximately half of them (50.5%) indicated ‘Medication(s) are expensive and difficult to afford’ and/or ‘Insurance does not provide coverage when cost exceeds the limit’ as the barrier for taking NUCs. Although entecavir has a higher cost, research has shown that entecavir is still more cost-effective than other NUCs [38]. One study evaluated the cost-effectiveness of NUCs in China, and assessed the thresholds at which the drugs would be cost-saving to the national treatment program [39].…”
Section: Discussionmentioning
confidence: 99%
“… 11 China is one of the countries with a high incidence, millions of patients with liver dysfunction undergo surgery annually. 12 Therefore, patients with diverse liver dysfunction are common in clinical practice in China. 13 Various physiological functions of the liver may be affected by liver dysfunction, such as material metabolism, bile synthesis and secretion, detoxification, and immune response.…”
Section: Introductionmentioning
confidence: 99%